ORGANIZATION OF THE WORK ON THE POPULARIZATION, MOTIVATION AND SUPPORT OF BREAST FEEDING IN PRIMORSKI TERRITORY - T.I. Burmistrova (Вопросы современной педиатрии, 2006)
In 1996 in Primorski territory the first strides were made on the popularization of breast feeding, rooming; in 1998 the center of protection, support and popularization of breast feeding was established. Now in the territory there are nine obstetrics institutions which are titled «friendly to the child hospital». In Arsenyev city all obstetrics and children's institutions have this title. This approach let decrease morbidity, especially of the diseases related with a feeding pattern (infectious and parasitic diseases, blood diseases, disorders of the endocrine system, respiratory, digestive and urogenital organs). Whereas the common sickness rate of children under one year in Primorski territory had increased from 1996 to 2005 by 17,3%, in Arsenyev — by 15,2%. The illness ratio of children under one year in Arsenyev had been changed: the incidence of diseases, directly or indirectly related with the feeding kind, had decreased: pneumonia — 12,3 times (from 2,22 to 0,18%), enteric infections — 1,96 times (from 0.51 to 0,26%). Key words: breast feeding, morbidity of children under one year, «friendly to the child hospital».